Analysis and security management of telecommunication systems based on predictive technologies - Kozlovskii, V. V.; Ivanov, O. V.; Snizhko, V. V. (Science-based technologies, 2018)
This paper presents the peculiarities of providing information, taking into account the subjective aspect of this process. The main purpose of the study is to develop an algorithm for analyzing and managing integrated security, which will unify the approaches to information security management. Security does not exist by itself, in isolation from a person. It is provided for a person and it is appreciated. Therefore, the notion of security has not only an objective but also a subjective aspect, since the assessment of its level is ultimately man. Using cognitive modeling methods can greatly improve the analysis and management of the security of the telecommunication system. The advantages of the cognitive approach are the ability to simulate poorly structured (poorly formalized) systems that are characterized by incomplete or uncertain knowledge of them. The application of the developed algorithm will allow the specialists to begin to develop appropriate computational procedures and modules, which can be further used in telecommunication system security. The results of the research will be useful for information security specialists.